KEPENTINGAN YUNANI BERGABUNG KE DALAM CHINA-CENTRAL AND EASTERN EUROPEAN COOPERATION (CCEEC) TAHUN 2019 - Rachmaesya Maulya; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The global financial crisis experienced by the world has had an impact on the stability of the Greek economy, causing Greece to face debt default. Forcing the Greek gov-ernment to change the direction of the economy by warmly welcoming investment from Chinese companies. China has expressed interest in the port of Pireaus which is an important route for China to enter the European market. China formed subregional cooperation in Eastern and Central Europe and persuaded Greece to join and prom-ised Greek economic stability to return. In discussing the problem of this research, the author uses qualitative research methods, data collected using data library research, with the perspective of neoliberal-ism and the state as the level of analysis and supported by the theory of international cooperation. The results of this study show that there are economic and political influences in the cooperation between Greece and China through CCEEC. Greece decided to join the CCEEC in order to restore the Greek economy that had been devastated by the debt crisis. The cooperation carried out includes investing in the development of Greek state infrastructure and stabilizing the Greece. Keywords: Cooperation CCEEC, Economic Crisis, China, European Union